State-profession relation in Bangladesh: the development of primary education and teaching occupation, 1971-2001 - Quddus, S. M. Abdul (Silverfish Books, 2017)
Bangladesh has the Westminster type of political system, where the prime minister is the main executive, leader of the house and advises the president. The civil service is the administrative arm of the government and has the responsibility to serve the people of the country (GoB, 1994: Art 21). However, the structure of Bangladesh Civil Service shows a rigid pattern of ranks which correspondence to occupational type hence financial benefit, privileges, honours and power. The horizontal classification of civil service is also based on number of other factors such as educational requirements, level of responsibility and so on. Civil servants in Bangladesh are categorized into four “Classes” among which higher level civil servants are recognized as Class I “gazetted officers”. Below them are three other classes namely Class II, Class III, and Class IV “employees” performing jobs of varied responsibility. But less privileges, honour, and rewards are attached to these three lower-level “classes”. It is to mention that higher skill or occupational expertise, autonomy or self-directing, exclusiveness etc are some essential attributes of members of professionalized occupation. Most importantly, occupational expertise that justifies privileges and higher status depend on the state and its policies i.e. how a state officially define and classify particular kinds of work in the national labour market (Freidson, 2001:128). In this paper, I shall explore the development of the vocational situation in a historical context of primary schoolteachers particularly related with their position in the civil service system in Bangladesh. My discussion will also cover the following two basic questions: (a) How historically primary teaching occupation has taken shape particularly in relation to civil service system in Bangladesh? In other words, to what extent primary schoolteachers’ position in the country’s civil service system put them in an unfavourable situation to achieve qualities of members of a professionalized occupation; (b) to what extent different political regimes perceived primary teaching as a self-directing occupation i.e. extended the opportunity for greater autonomy in performing teachers’ professional tasks since country’s independence. I think these are main two questions need to be answered in order to explain the development of primary education in general and teaching occupation in particular i.e. demeanour and standards of what teachers do and material rewards as well as social prestige that have been linked to primary schoolteachers’ jobs.